Trends in the Development of the Efficiency of Management of Higher Education Institutions in Uzbekistan - Odinayeva N. F. (International Journal on Orange Technologies, 2023)
In recent years, large-scale reforms have been implemented in our country to increase the level of coverage of the population with higher education services, and to improve the quality indicators of the educational services provided to the population. In particular, President Mirziyoyev has set the task of "developing public-private partnership in the field of higher education, increasing the level of coverage with higher education from 50 percent based on the organization of state and non-state higher education institutions in the regions, and creating a healthy competitive environment in the field" until 2030 will prove the ongoing reforms indicate that the follower will continue in the following years.